Toward Low-Emission Agriculture: Synergistic Contribution of Inorganic Nitrogen and Organic Fertilizers to GHG Emissions and Strategies for Mitigation - Shahzad Haider; Jiajie Song; Jinze Bai; Xing Wang; Guangxin Ren; Yuxin Bai; Yuming Huang; Tahir Shah; Yongzhong Feng (Plants)
Nitrogen (N) and organic-source fertilizers in agriculture are important to sustain crop production for feeding the growing global population. However, their use can result in significant greenhouse gas (GHG) emissions, particularly carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O), which are important climate drivers. This review discusses the interactive effects, uncovering both additive and suppressive outcomes of emissions under various soil and climatic conditions. In addition to examining the effects of nitrogen and the nitrogen use efficiency (NUE), it is crucial to comprehend the mechanisms and contributions of organic fertilizers to GHG emissions. This understanding is vital for developing mitigation strategies that effectively reduce emissions while maintaining agricultural productivity. In this review, the current knowledge is utilized for the management of nitrogen practices, such as the optimization of fertilization rates, timing, and methods of application, in terms of the nitrogen use efficiency and the related GHG emissions. Moreover, we discuss the role of organic fertilizers, including straw, manure, and biochar, as a mitigation strategy in relation to GHG emissions through soil carbon sequestration and enhanced nutrient cycling. Important strategies such as crop rotation, tillage, irrigation, organic fertilizers, and legume crops are considered as suitable approaches for minimizing emissions. Even with the progress made in mitigating fertilizer-related emissions, research gaps remain, specifically concerning the long-term effect of organic fertilizers and the interactions between microbial communities in the soil and fertilization practices. Furthermore, the differences in application practices and environmental conditions present considerable obstacles to accurate emission quantification. This review underlines the importance of conducting more thorough research on the combined application of N and organic fertilizers in multiple cropping systems to evolve region-specific mitigation strategies.